Design and Validation of CMOS Atom Chips for Electronics and Sensor Integration in Cold Atom Devices - New, Joshua (2025)
Cold atoms have proven to be a promising medium for numerous sensing and timing applications. Atomic clocks have provided the definition of the second since the 1960s and are essential for navigation and telecommunications. Increasingly precise clocks are capable of measuring small changes in the gravitational potential, which can be used to detect seismic activity, and atomic clock networks have been suggested for detecting dark matter. Cold atom-based gyroscopes have already demonstrated stability comparable to light-based gyroscopes, with the potential to exceed them.